2009
DOI: 10.1111/j.1600-0633.2009.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seasonal, diel, lunar, and other environmental factors on upstream fish passage in the Igarapava Fish Ladder, Brazil

Abstract: Upstream fish passage was evaluated during 12 months in the vertical-slot Igarapava Fish Ladder constructed around Igarapava Dam, in the heavily dammed Grande River, Southeast Brazil. A video monitoring system was used to observe 61,621 fish that passed the ladder, of which 93.5% were identified to 15 taxa. Among the migratory species, the most abundant were Pimelodus maculatus (33.6% of all fish), Leporinus octofasciatus (31.4%), Leporinus friderici (4.5%), and Prochilodus lineatus (3.1%). Seven taxa were cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 33 publications
0
28
0
1
Order By: Relevance
“…The gravitational pull of the moon causes tides, which have profound effects on community structure (Kruse, Taylor, Muhando, & Reuter, ; Zimecki, ). However, in streams, the moon's gravitational effect on water is insignificant, and fish movements are related to the luminosity of the different moon phases: diurnal species are active during the full moon, whereas many nocturnal species are active during new and quarter‐moon phases (Bizzotto et al., ). The low melatonin levels of nocturnal fish inhibit their activity during nights with a full moon (Oliveira, Duncan, Pousão‐Ferreira, Mañanós, & Sánches‐Vázquez, ; Takemura et al., ; Zimecki, ); therefore, the high activity levels of A .…”
Section: Discussionmentioning
confidence: 99%
“…The gravitational pull of the moon causes tides, which have profound effects on community structure (Kruse, Taylor, Muhando, & Reuter, ; Zimecki, ). However, in streams, the moon's gravitational effect on water is insignificant, and fish movements are related to the luminosity of the different moon phases: diurnal species are active during the full moon, whereas many nocturnal species are active during new and quarter‐moon phases (Bizzotto et al., ). The low melatonin levels of nocturnal fish inhibit their activity during nights with a full moon (Oliveira, Duncan, Pousão‐Ferreira, Mañanós, & Sánches‐Vázquez, ; Takemura et al., ; Zimecki, ); therefore, the high activity levels of A .…”
Section: Discussionmentioning
confidence: 99%
“…Sampling in the ladder occurred bimonthly during daylight hours, from November 2007 to October 2008. Previous studies have reported higher fish abundance in ladders during daytime (Fernandez et al, 2007;Bizzoto et al, 2009), even though Siluriformes species are more active at night. Bimonthly captures were combined within months and expressed as fish/m 2 .…”
Section: Data Collectionmentioning
confidence: 97%
“…Initiation of spawning migrations into streams and the timing of reproduction in fishes represent important behavioural decisions that are elicited by external cues such as seasonal photoperiod (Quinn & Adams, 1996; Bizzotto et al , 2009) and other environmental variables (Kamler, 2002). There is strong selection for adults to reproduce at times and in locations that are conducive to offspring survival.…”
Section: Introductionmentioning
confidence: 99%